HUBUNGAN INDEKS MASSA TUBUH DENGAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI POLI JANTUNG RUMAH SAKIT HUSADA UTAMA SURABAYA - Melliya Sari, Gevi; Eko Kurniawan, Vendi; Puspita, Enny; Devi Amalia, Sari (LPPM STIKES HUSADA JOMBANG, 2023)
Hypertension is a world health issue that has been dubbed the silent killer disease. One of the factors that influence the incidence of hypertension is body weight. Body mass index is very influential on the incidence of hypertension, where excess body mass index can trigger the occurrence of hypertension risk factors that are higher than someone with a normal body mass index. The purpose of this study was to determine the relationship between body mass index and blood pressure in patients with hypertension The research design used analytic with cross sectional approach. The sample in this study was some hypertensive patients who visited the cardiac polyclinic of Husada Utama Hospital Surabaya during June-July 2022 who met the research criteria as many as 85 respondents. The sampling technique used non-probability sampling method with a purposive sampling approach. The dependent variable in this study was body mass index. The independent variable in this study was blood pressure. The data collection instruments used in this study were questionnaire sheets and observation sheets. Test data analysis using the Spearman Rho rank test. From the results of the Spearman Rho rank correlation test, the value of sig (2-tailed) is 0.000 < (0.05), so the research hypothesis is accepted which means that there is a relationship between body mass index and blood pressure in patients with hypertension at the Cardiology Clinic of Husada Utama Hospital Surabaya with correlation strength in the strong category (0.629). Proper management of body mass index will prevent a person from the risk of an increase in blood pressure and avoid the risk of non-communicable diseases